2012
DOI: 10.1021/es3001695
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Balanced Fertilization Decreases Arbuscular Mycorrhizal Fungal Diversity in an Arable Soil in North China Revealed by 454 Pyrosequencing

Abstract: A balanced fertilization can increase crop yields partly due to stimulated microbial activities and growths. In this study, we investigated arbuscular mycorrhizal fungi (AMF) in arable soils to determine the optimal practices for an effective fertilization. We used pyrosequencing-based approach to study AMF diversity, as well as their responses to different long-term (>20 years) fertilizations, including OM (organic manure) and mix chemical fertilizers of NP (nitrogen-phosphorus), NK (nitrogen-potassium), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
174
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(195 citation statements)
references
References 39 publications
15
174
1
5
Order By: Relevance
“…The lack of response was particularly unexpected, as large reductions in AMF abundance except for spore density had been observed in response to P fertilizer application. Dissimilar results were found in other studies that P fertilization markedly modified AMF biodiversity in a tropical savanna forage system (Alguacil et al, 2010) and agricultural ecosystems (Lin et al, 2012;Gosling et al, 2013). These different observations indicate that the AMF species composition in response to P additions may vary in different ecosystems.…”
Section: Effects Of Fertilization On Amf Abundance and Community Strumentioning
confidence: 47%
See 2 more Smart Citations
“…The lack of response was particularly unexpected, as large reductions in AMF abundance except for spore density had been observed in response to P fertilizer application. Dissimilar results were found in other studies that P fertilization markedly modified AMF biodiversity in a tropical savanna forage system (Alguacil et al, 2010) and agricultural ecosystems (Lin et al, 2012;Gosling et al, 2013). These different observations indicate that the AMF species composition in response to P additions may vary in different ecosystems.…”
Section: Effects Of Fertilization On Amf Abundance and Community Strumentioning
confidence: 47%
“…Previous studies using morphological (EgertoneWarburton andAllen, 2000, 2007;Bhadalung et al, 2005) and molecular identifications of AMF (Jumpponen et al, 2005;Porras-Alfaro et al, 2007;Lin et al, 2012;Liu et al, 2012) have shown that increased N fertilizer induced changes in AMF species richness and community structure. P fertilizer applications can also lead to changes in AMF community structures (Alguacil et al, 2010;Lin et al, 2012;Liu et al, 2012). However, most of these studies have examined the response of AMF communities to either single elements (N or P) or a combination of N and P, but the interactive effects of the two elements have rarely been examined.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…By using 454 pyrosequencing, an average of 37.8 AM fungi was obtained from each of 17 woody plant species (Chen et al 2017), and an average of 32.8 EM fungi was found in each of 12 mixed root samples (Gao et al 2015) in a subtropical forest. In the agro-ecosystems, there were average 10−16 and 22−27 AM fungi observed in maize or rice root and soil samples, by using terminal restriction fragment length polymorphism and/or clone library analyses (Liu et al 2014, 2016; Wang et al 2015), but an average 29−49 AM fungi was detected in soil samples by using 454 pyrosequencing technique (Lin et al 2012). In the grassland ecosystems, a total of 34−37 AM fungi was obtained from mixed plant root samples in alpine meadow ecosystems via clone library method (Liu et al 2012b; Yang et al 2013).…”
Section: Mycorrhizal Fungal Diversitymentioning
confidence: 99%
“…For example, warming had neutral, negative or positive effects on AM fungal root colonisation rate, spore density, extra-radical hyphal (ERH) density, and richness (Yang et al 2013, 2016; Kim et al 2014, 2015; Gao et al 2016; Shi et al 2017a), and changed AM fungal community composition in soil rather than in root (Yang et al 2013) in grassland ecosystems. Fertilisation (nitrogen, phosphorus, or organic manure) significantly decreased AM fungal root colonisation rate, spore density and ERH diversity, and altered AM fungal community composition in agricultural (Lin et al 2012) and grassland (Liu et al 2012b; Zheng et al 2014; Kim et al 2015) ecosystems. Increased precipitation could significantly increase AM fungal root colonisation rate, spore density, and ERH density, decrease AM fungal diversity, and changed AM fungal community composition in grassland ecosystems (Li et al 2015; Gao et al 2016).…”
Section: Mycorrhizal Fungal Response To Global Changementioning
confidence: 99%